Investıgatıon of the Effects of Exercıse and Kınesıo Bandıng on the Backache - Emrah Yilmaz, Abdulsamet Efdal, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction. This study aims to investigate the effects of Kinesio banding on backache and flexibility in addition to exercise therapy for sedentary women with chronic mechanical backache. Material and methods. A total of 20 sedentary women participated in the study voluntarily. The women in the subject group were applied both Kinesio band and exercise, while the control group was applied only the same exercise program as the subject group. Results. The results of statistical analysis revealed that exercise and Kinesio banding created a more positive difference in flexibility and backache values in the subject group compared to the control group (p <0.05). It was determined that the application of the Kinesio band applied together with exercise is a more effective method in sedentary women with chronic backache. Conclusions. We think that continuing the study with more participants and for a long time will make significant contributions to the literature by producing more positive results.